Tajemnice Września - Karolak, Sylwia (Przestrzenie Teorii, 2023)
The author indicates that a research reflection on the civilian experience of September 1939, as recorded in the pages of Polish literature, will make it possible to complete the picture that emerges from previous analyses, dominated by the soldier’s, military experience. This work requires a broader view of the events of the beginning of the war, going beyond the meanings and time defined by military actions. Seen in this way, literary September appears as an as yet undiscovered mystery.